2018
DOI: 10.5607/en.2018.27.6.526
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Aggression-related Responses on EEG and ECG

Abstract: Gender differences in aggression viewed from an evolutionary and sociocultural perspective have traditionally explained why men engage in more direct and physical aggression, and women engage in more indirect and relational aggression. However, psychological and behavioral studies offer inconsistent support for this theory due to personal or social factors, and little is known about the gender-based neurobiological mechanisms of aggression. This study investigates gender differences in aggression through an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Gamma oscillations can provide an ideal mechanism to coordinate precise neural coding within and across brain structures because of their fast temporal dynamics [ 32 ]; thus, these oscillations are tied to a diverse array of neural functions, including attention, working memory, sensory processing, action selection, movement initiation and decision making [ 32 , 33 , 34 ]. Interestingly, compared with women, men usually exhibit more aggressive behaviors and greater gamma signals in the right ventrolateral frontal cortex evoked by aggressive videos [ 62 ]. Consistent with this, the present results show that the socially isolated mice exhibited significantly greater gamma activities compared with the cohousing mice, and the gamma power spectra in the right VMH of the socially isolated mice during attack was significantly greater than that during pre-attack periods.…”
Section: Discussionmentioning
confidence: 99%
“…Gamma oscillations can provide an ideal mechanism to coordinate precise neural coding within and across brain structures because of their fast temporal dynamics [ 32 ]; thus, these oscillations are tied to a diverse array of neural functions, including attention, working memory, sensory processing, action selection, movement initiation and decision making [ 32 , 33 , 34 ]. Interestingly, compared with women, men usually exhibit more aggressive behaviors and greater gamma signals in the right ventrolateral frontal cortex evoked by aggressive videos [ 62 ]. Consistent with this, the present results show that the socially isolated mice exhibited significantly greater gamma activities compared with the cohousing mice, and the gamma power spectra in the right VMH of the socially isolated mice during attack was significantly greater than that during pre-attack periods.…”
Section: Discussionmentioning
confidence: 99%
“…Aggression was recently defined as "the feelings of anger or antipathy resulting in hostile or violent behavior" by Im et al [17]. The manifestation of aggression has been widely studied by using aggression paradigms [35] and self-report questionnaires [5].…”
Section: Discussionmentioning
confidence: 99%
“…For nearly three decades, the Buss-Perry questionnaire [5] has been one of the most commonly used instruments for assessing aggression with confirmed statistical relevance. Most studies revealed that aggressive tendencies of males, especially in physical and direct subdomains of aggression were more prominent than females, and under unprovoked conditions [2,3,17]. We used an adapted version of the Buss-Perry questionnaire [6], and found that general aggression scores of males were significantly higher than the scores of females.…”
Section: Discussionmentioning
confidence: 99%
“…The results of one study on gender differences in aggression using electroencephalography (EEG) and electrocardiography (ECG) analysis showed that physical and reactive/overt aggression was stronger in men. In addition, aggressive videos revealed prominent gender-related patterns in γ -signals [ 20 ]. As well as, Fahlgren et al reported that aggression was significantly related to trait anger only for male [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the school level, factors such as negative attitudes towards school and school staff and negative social relationships with classmates can also be mentioned. At the family level, factors such as lack of emotional cohesion among family members and negative economic and social conditions were effective in the occurrence of aggressive behavior [ 20 ]. Even, parental support can have a positive effect, especially in relation to adolescent cognitive development and behavior in the school environment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%